Postcinematic vision : the coevolution of moving-image media and the spectator - Cook, Roger F., 1948- (Posthumanities, 2020)
"A study of how film has continually intervened in our sense of perception, with far-ranging insights into the current state of lived experience How has cinema transformed our senses, and how does it continue to do so? Positing film as a stage in the long coevolution of human consciousness and visual technology, Postcinematic Vision offer a fresh perspective on the history of film while providing startling new insights into the so-called divide between cinematic and digital media. Starting with the argument that film viewing has long altered neural circuitry in our brains, Roger F. Cook proceeds to reevaluate film's origins, as well as its merger with digital imaging in the 1990s. His animating argument is that film has continually altered the relation between media and human perception, challenging the visual nature of modern culture in favor of a more unified, pan-sensual way of perceiving. Through this approach, he makes original contributions to our understanding of how mediation is altering lived experience. Along the way, Cook provides important reevaluations of well-known figures such as Franz Kafka, closely reading cinematic passages in the great author's work; he reassesses the conventional wisdom that Marshall McLuhan was a technological determinist; and he lodges an original new reading of The Matrix. Full of provocative and far-reaching ideas, Postcinematic Vision is a powerful work that helps us see old concepts anew while providing new ideas for future investigation"--Publisher's description